Faktor-Faktor dalam Mendeteksi Kecurangan pada Laporan Keuangan dengan Metode Fraud Diamond - Tommy Ana Ximenes; Umar Issa Zubaidi (Media Bisnis, 2021)
The purpose of this research is to obtain empirical evidence regarding the effect of financial stability, external pressure, financial targets, the nature of the industry, effective monitoring, change of auditors, change of directors, institutional ownership and quality of external auditors as independent variables in detecting the likelihood of fraudulent financial reporting using fraud diamond methods. The population used in this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018-2020. The sample used for this research consists of 40 listed manufacturing companies. The selection of these sample used the purposive sampling method with total 120 data and to analyze the data using multiple regression analysis. The research findings reveal that the nature of the manufacture industry and quality of external auditor are proven to have an influence in detecting the likelihood of fraudulent financial reporting. In the meantime, financial stability, external pressure, financial targets, effective monitoring, auditor turnover, change of directors and institutional ownership have no influence in detecting the likelihood of fraudulent financial reporting.